Legal Assistance for Workers in Reporting Violations of Religious Holiday Allowance (THR) as an Effort to Protect Normative Labor Rights in Surabaya - Cenuk Sayekti; Hariyono Hariyono; Hijjrah Saputra (Universitas Negeri Semarang, 2026)
Violations in the payment of Religious Holiday Allowance (Tunjangan Hari Raya/THR) remain a recurring issue in labor practices in Indonesia, including in Surabaya. This community service program aims to enhance workers’ access to justice through legal awareness and assistance in reporting THR violations. The methods employed include participatory legal education, complaint clinics, and case-based assistance. The results indicate an increase in workers’ understanding of their normative rights and a growing willingness to report violations. Empirical data show that in 2024, there were 26 complaints involving 1,203 affected workers, while in 2025 the number increased to 56 complaints involving 1,811 workers. These findings suggest that THR violations remain systemic and require sustained legal intervention through community-based assistance mechanisms.